Anthralin Suppresses the Proliferation of Influenza Virus by Inhibiting the Cap-Binding and Endonuclease Activity of Viral RNA Polymerase - Hu, Ao; Li, Jing; Tang, Wei; Liu, Ge; Zhang, Haiwei; Liu, Chunlan; Chen, Xulin (Frontiers in Microbiology, 2020)
Influenza virus RNA-dependent RNA polymerase (vRdRp) does not have capping activity and relies on the capped RNAs produced by the host RNA polymerase II (RNAPII). The viral polymerases process the capped RNAs to produce short capped RNA fragments that are used as primers to initiate the transcription of viral mRNAs. This process, known as cap-snatching，can be targeted by antiviral therapeutics. Here, anthralin was identified as an inhibitor against influenza a virus (IAV) infection by targeting the cap-snatching activity of the viral polymerase. Anthralin, an FDA-approved drug used in the treatment of psoriasis, shows antiviral activity against IAV infection in vitro and in vivo. Importantly, anthralin significantly reduces weight loss, lung injury, and mortality caused by IAV infection in mice. The mechanism of action study revealed that anthralin inhibits the cap-binding function of PB2 subunit and endonuclease activity of PA. As a result, viral mRNA transcription is blocked, leading to the decreases in viral RNA replication and viral protein expression. In con-clusion, anthralin has been demonstrated to have the potential of an alternative antivi-ral against influenza virus infection. Also, targetting the captive pocket structure that includes the N-terminus of PA endonuclease domain and the C-terminal of PB2 cap-binding domain of IAV RdRp may be an excellent strategy for developing anti-influenza drugs.